1998
DOI: 10.1046/j.1365-2249.1998.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Different susceptibilities of yeasts and conidia ofPenicillium marneffeito nitric oxide (NO)-mediated fungicidal activity of murine macrophages

Abstract: Penicillium marneffei is an important opportunistic fungal pathogen. Host defence mechanisms against P. marneffei are not fully understood. We investigated the fungicidal activity of murine peritoneal macrophages against two forms of P. marneffei, conidia and yeast cells, and the involvement of the NO-mediated killing system. Peritoneal macrophages suppressed the intracellular growth of P. marneffei yeast cells and conidia. The number of live yeast cells within macrophages was significantly reduced by activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 46 publications
(54 reference statements)
2
41
0
Order By: Relevance
“…This effect was more clearly related to the induction of iNOS in the former cells than that in the latter cells. However, in both cases, it could be mimicked by SNP addition, confirming the important anti-P. marneffei activity of reactive nitrogen intermediates (3,8).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…This effect was more clearly related to the induction of iNOS in the former cells than that in the latter cells. However, in both cases, it could be mimicked by SNP addition, confirming the important anti-P. marneffei activity of reactive nitrogen intermediates (3,8).…”
mentioning
confidence: 56%
“…Macrophages and T lymphocytes play a central role in host resistance to P. marneffei (7). We and others recently reproduced in vitro at 37°C the intracellular growth of P. marneffei as yeast and showed that activated J774 macrophages inhibit yeast transformation of P. marneffei conidia by the secretion of NO (3,8). In view of the interplay between NO and iron, we studied the role of iron on (i) the in vitro growth requirement of P. marneffei and (ii) the fungicidal activity of activated human and mouse macrophages.…”
mentioning
confidence: 97%
“…Five isolates of P. marneffei were isolated from the lungs of 10 bamboo rats. P. marneffei was identified by the appearance of the fungal colonies on Sabouraud dextrose agar at 25°C and by microscopic examination (9).…”
mentioning
confidence: 99%
“…Previously, BHI medium was commonly used to generate P. marneffei yeast cells 6,7 . These cells develop via arthroconidiation, a process whereby conidia differentiate to hyphal cells that subsequently divide into arthroconidia by septal (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its transition ability was investigated daily when 1% peptone was added to the YNB supplemented with 0.1%, 0.5%, 1%, 2%, or 4% glucose and to the YNB supplemented with 1 mM, 2.5 mM, 5 mM, or 10 mM GlcNAc. 7 conidia were inoculated into a 250-ml flat bottom flask containing 50 ml of the tested liquid media. The culture was incubated in a gyratory shaker (New Brunswick Scientific Co., Inc.) at 37°C, 120 rpm.…”
Section: Preparation Of Inoculum Preparation Of Inoculum Preparation mentioning
confidence: 99%